2014
DOI: 10.5194/bg-11-5763-2014
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nitrogen and organic matter during primary succession of <i>Leymus arenarius</i> dunes on the volcanic island Surtsey, Iceland

Abstract: Abstract. Initial soil development and enhanced nutrient retention are often important underlying environmental factors during primary succession. We quantified the accumulation rates of nitrogen (N) and soil organic matter (SOM) in a 37-year-long chronosequence of Leymus arenarius dunes on the pristine volcanic island Surtsey in order to illuminate the spatiotemporal patterns in their build-up. The Leymus dune area, volume and height grew exponentially over time. Aboveground plant biomass, cover or number of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Despite the fact that the median R / S ratio outside the colony was almost three times higher than the upper extreme for cool temperate deserts reported by Mokany et al (2006), it corresponded closely with the mean ratio of 19 reported by (Stefansdottir et al, 2014) for the Leymus area outside the seabird colony. For the grassland inside the colony, the median R / S of 5 did not differ much from the median reported by Mokany et al (2006) for cool temperate grasslands without bird colonies.…”
Section: Shifts From Belowground To Aboveground Plant Biomasssupporting
confidence: 76%
See 3 more Smart Citations
“…Despite the fact that the median R / S ratio outside the colony was almost three times higher than the upper extreme for cool temperate deserts reported by Mokany et al (2006), it corresponded closely with the mean ratio of 19 reported by (Stefansdottir et al, 2014) for the Leymus area outside the seabird colony. For the grassland inside the colony, the median R / S of 5 did not differ much from the median reported by Mokany et al (2006) for cool temperate grasslands without bird colonies.…”
Section: Shifts From Belowground To Aboveground Plant Biomasssupporting
confidence: 76%
“…Despite the very sparse aboveground vegetation cover, it became evident during sampling that the unvegetated tephra sand areas were fully colonized by roots. Another study, which took place on and around Leymus dunes in the same area outside the seagull colony, but not within our permanent study plots, found similar dense root distribution (Stefansdottir et al, 2014). Therefore, we can assume that after vegetation establishment the N retention on Surtsey has increased and is now close to the Table 1.…”
Section: Nitrogen Accumulation Outside the Seabird Colonymentioning
confidence: 49%
See 2 more Smart Citations
“…With time, lyme grass dunes slowly accumulate N from the surrounding area with an extensive root system (Leblans et al 2014, Stefansdottir et al 2014). The buildup of N within the dunes originating from atmospheric deposition averages 0.66 g N m -2 y -1 (Stefansdottir et al 2014) but within seagull colonies the rate of N buildup within lyme grass is much faster or 4.7 g N m -2 y -1 (Leblans et al 2014). Gradually, therefore, lyme grass probably changes from being predominantly N limited to being largely P limited.…”
Section: Discussionmentioning
confidence: 99%